Association of pre‐operative brain pathology with post‐operative delirium in a cohort of non‐small cell lung cancer patients undergoing surgical resection. Issue 9 (4th March 2013) - Root, James C.; Pryor, Kane O.; Downey, Robert; Alici, Yesne; Davis, Marcus L.; Holodny, Andrei; Korc‐Grodzicki, Beatriz; Ahles, Tim
Abstract Objective Post‐operative delirium is associated with pre‐operative cognitive difficulties and diminished functional independence, both of which suggest that brain pathology may be present in affected individuals prior to surgery. Currently, there are few studies that have examined imaging correlates of post‐operative delirium. To our knowledge, none have examined the association of delirium with existing structural pathology in pre‐operative cancer patients. Here, we present a novel, retrospective strategy to assess pre‐operative structural brain pathology and its association with post‐operative delirium. Standard of care structural magnetic resonance imaging (MRIs) from a cohort of surgical candidates prior to surgery were analyzed for white matter hyperintensities and cerebral atrophy. Methods We identified 23 non‐small cell lung cancer patients with no evidence of metastases in the brain pre‐operatively, through retrospective chart review, who met criteria for post‐operative delirium within 4 days of surgery. 24 age‐ and gender‐matched control subjects were identified for comparison to the delirium sample. T1 and fluid‐attenuated inversion recovery sequences were collected from standard of care pre‐operative MRI screening and assessed for white matter pathology and atrophy. Results We found significant differences in white matter pathology between groups with the delirium group exhibiting significantly greater white matter pathology than the non‐delirium group. Measure of cerebral atrophy demonstrated no significant difference between the delirium and non‐delirium group. Conclusions In this preliminary study utilizing standard of care pre‐operative brain MRIs for assessment of structural risk factors to delirium, we found white matter pathology to be a significant risk factor in post‐operative delirium. Limitations and implications for further investigation are discussed. Copyright © 2013 John Wiley & Sons, Ltd.